THE EFFECTIVE USE OF JIGSAW IN TEACHING DESCRIPTIVE TEXT WRITING - Aprianti, Nita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractTask Based Language Teaching is an approach in which task as its main course. Jigsaw is one of the techniques in the umbrella of TBLT which allows students and teacher to make a cooperative learning environment in the classroom. Teaching a descriptive text using Jigsaw is considered effective for the students in the classroom. The research was conducted to the 8th grade students of SMPN 5 Pontianak in academic year 2016/2017 and the subject were the eighth grade students from class C. This research was conducted through pre- experimental research. The result of the research showed that Jigsaw is effective to be used in teaching descriptive text writing. The result showed the t-test result (4.690) was higher that the t-value (2.042). The effect size result also showed a moderate effect based on Burns’ classification (0.2ES 0.8). It was also found from three aspects of scoring, grammar, content and organization that has moderate effect on grammar and organization while in content it was highly effective. Keyword: Jigsaw, Descriptive Text, Writing